Evaluating access to essential medicines for treating childhood cancers: a medicines availability, price and affordability study in New Delhi, India - Rohina Joshi; Neha Faruqui; Alexandra Martiniuk; Abhishek Sharma; Chanchal Sharma; Bhumika Rathore; Ramandeep Singh Arora (BMJ Global Health)
Introduction Limited access to essential medicines (EMs) for treating chronic diseases is a major challenge in low-income and middle-income countries. Although India is the largest manufacturer of generic medicines, there is a paucity of information on availability, price and affordability of anti-neoplastic EMs, which this study evaluates.Methods Using a modified WHO/Health Action International methodology, data were collected on availability and price of 33 strength-specific anti-neoplastic EMs and 4 non-cancer EMs. Seven ‘survey anchor’ hospitals (4 public and 3 private) and 32 private-sector retail pharmacies were surveyed. Median price ratios (MPRs) were calculated by comparing consumer prices with international reference prices (IRPs).Results On average, across survey anchor areas (hospital and private-sector retail pharmacies combined), the mean availability of anti-neoplastic EMs and non-cancer medicines was 70% and 100%, respectively. Mean availability of anti-neoplastic EMs was 38% in private-sector retail pharmacies, 43% in public hospital pharmacies and 71% in private hospital pharmacies. Median MPR of lowest-priced generic versions was 0.71 in retail pharmacies. The estimated cost of chemotherapy medicines needed for treating a 30 kg child with standard-risk leukaemia was INR 27 850 (US$442) and INR 17 500 (US$278) for Hodgkin’s lymphoma, requiring 88 and 55 days’ wages, respectively, for the lowest paid government worker.Conclusion Most anti-neoplastic EMs are found in survey anchor areas, however, mean availability was less than non-cancer medicines; not meeting the WHO target of 80%. Medicine prices were relatively low in New Delhi compared with IRPs. However, the cost of chemotherapy medicines seems unaffordable in the local context.